CH3NH3PbI(3-x)(BF4)(x): molecular ion substituted hybrid perovskite - Nagane, Satyawan; Bansode, Umesh P.; Game, Onkar S.; Chhatre, Shraddha; Ogale, Satishchandra (Chemical Communications, 2014)
A molecular ion (BF4-) substituted hybrid perovskite CH3NH3PbI(3-x)(BF4)(x) is synthesized. The substituted perovskite shows significant enhancement in electrical conductivity at low frequencies and improved photoresponse under AM1.5 illumination as compared to the perovskite (CH3NH3PbI3).